Clinical and Epidemiological Aspects of Parkinson's Disease in the South of Western Siberia - Rozhdestvensky, Alexey Sergeevich; Delov, Roman Andreevich; Marks, Elena Andreevna; Gaponenko, Ivan Aleksandrovich; Khanokh, Elena Vladimirovna (Frontiers in Neurology, 2020)
Background: The article is devoted to one of the most common neurodegenerative diseases in the world—Parkinson's disease (PD), the prevalence of which in Russia reaches 140–150 people per 100,000 people. The clinical and anamnestic profile of a patient with PD is presented, the prevalence of motor and non-motor symptoms is reflected, and a comparative characteristic of the neurological deficit in the Siberian population of patients with other cohorts of patients with Parkinson's disease in different countries and ethnic groups is presented. Methods: We studied 140 patients with Parkinson's disease. A comprehensive assessment of neurological status was performed using the “Unified Parkinson's Disease Rating Scale (UPDRS).” In addition, we used the Beck Depression and MoCA scale test. Assessment of the presence and severity of olfactory dysfunction was performed using the Sniffin Stick odor identification test. The stage of PD was evaluated according to the classification of M. M. Hoehn and M. D. Yahr. Results: The cohort of the study was dominated by overweight patients with a higher level of education, with concomitant arterial hypertension, coronary heart disease, and dyslipidemia. The severity of motor and most non-motor symptoms directly correlates with the duration of PD and the stage of the disease. The predominant form of the disease was a mixed form, which was also noted in research cohorts in Canada and the UK. The Siberian cohort tends to be more prevalent in hyposmia, daytime sleepiness, orthostatic hypotension, and depressive and REM disorders. Conclusion: Our data show the importance of a comprehensive assessment of both motor and non-motor neurological deficits as well as the analysis of comorbid disorders and risk factors for the occurrence and progression of Parkinson's disease. They also show the prevalence of certain motor and non-motor symptoms in the Siberian cohort of patients with Parkinson's disease.